EC 22536-5304: a lead-rich and metal-poor long-period binary - Dorsch, Matti; Jeffery, C. S.; Irrgang, Andreas; Woolf, V.; Heber, Ulrich (Astronomy & Astrophysics, 2021)
Helium-burning hot subdwarf stars of spectral types O and B (sdO/B) are thought to be produced through various types of binary interactions. The helium-rich hot subdwarf star EC 22536-5304 was recently found to be extremely enriched in lead. Here, we show that EC 22536-5304 is a binary star with a metal-poor subdwarf F-type (sdF) companion. We performed a detailed analysis of high-resolution SALT/HRS and VLT/UVES spectra, deriving metal abundances for the hot subdwarf, as well as atmospheric parameters for both components. Because we consider the contribution of the sdF star, the derived lead abundance for the sdOB, + 6.3 +/- 0.3 dex relative to solar, is even higher than previously thought. We derive T-eff = 6210 +/- 70 K, log g = 4.64 +/- 0.10, [FE/H] = - 1.95 +/- 0.04, and [alpha/Fe] = + 0.40 +/- 0.04 for the sdF component. Radial velocity variations, although poorly sampled at present, indicate that the binary system has a long orbital period of about 457 days. This suggests that the system was likely formed through stable Roche lobe overflow (RLOF). A kinematic analysis shows that EC 22536-5304 is on an eccentric orbit around the Galactic centre. This, as well as the low metallicity and strong alpha enhancement of the sdF-type companion, indicate that EC 22536-5304 is part of the Galactic halo or metal-weak thick disc. As the first long-period hot subdwarf binary at [FE/H] less than or similar to- 1, EC 22536-5304 may help to constrain the RLOF mechanism for mass transfer from low-mass, low-metallicity red giant branch (RGB) stars to main-sequence companions.
CRIS-Team WoS Importer:2021-10-01